CHARACTERISTICS OF USING STATISTICAL METHODS IN TEACHING GEOGRAPHY - Makhmudjon Jalolitdinovich Boltayev (Western European Studies, 2024)
The article talks about the features of using statistical methods in teaching geography
Keywords: geography; teaching method; statistics; method